2013
DOI: 10.1016/j.jcf.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Safety and early treatment effects of the CXCR2 antagonist SB-656933 in patients with cystic fibrosis

Abstract: SB-656933 was well-tolerated in adult patients with cystic fibrosis. Patients receiving a daily dose of 50mg showed trends for improvement in sputum inflammatory biomarkers despite potential blunting of effects by lower than expected plasma concentrations. Although the increase in systemic inflammatory markers requires further evaluation, CXCR2 antagonism may be a useful approach for modulating airway inflammation in patients with cystic fibrosis. Clinical trial registered with www.clinicaltrials.gov (NCT00903… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 19 publications
1
80
0
Order By: Relevance
“…Moreover, these neutrophilic chemokines have been shown to be significantly elevated in the blood of CXCR2 knockout mice compared with wild-type littermates [49]. There is also recent clinical evidence that blood concentrations of IL-8 were significantly increased in a dose-dependent manner in patients with cystic fibrosis receiving a CXCR2 antagonist (SB-656933) [23], and in patients with bronchiectasis who received AZD5069 [24], further indicating a potential compensatory upregulation of CXCR2-specific ligands. Although the specific mechanisms regulating this systemic mediator release have not been investigated, a possible explanation of this observed adaptive increase could be a limited physiological compensatory response following blockade of CXCR2 receptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, these neutrophilic chemokines have been shown to be significantly elevated in the blood of CXCR2 knockout mice compared with wild-type littermates [49]. There is also recent clinical evidence that blood concentrations of IL-8 were significantly increased in a dose-dependent manner in patients with cystic fibrosis receiving a CXCR2 antagonist (SB-656933) [23], and in patients with bronchiectasis who received AZD5069 [24], further indicating a potential compensatory upregulation of CXCR2-specific ligands. Although the specific mechanisms regulating this systemic mediator release have not been investigated, a possible explanation of this observed adaptive increase could be a limited physiological compensatory response following blockade of CXCR2 receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Recent clinical studies demonstrated that a CXCR2 antagonist (AZD8309) given orally blocked the increase both in neutrophils (by 79%) and selected neutrophil chemoattractants, including IL-8 (by 52%), in induced sputum following inhaled LPS challenge [21], and significantly reduced LPS-induced neutrophil recruitment in the upper airways of healthy subjects [22]. Interestingly, however, treatment with the CXCR2 antagonists SB-656933 and AZD5069 caused a small but significant elevation in blood concentrations of IL-8 in studies of patients with cystic fibrosis and bronchiectasis, respectively [23,24]. Clinical data from a recent Phase 2b clinical trial showed that CXCR2 antagonism using MK-7123 can improve measures of lung function and reduce COPD exacerbations in current smokers but was associated with a decrease in absolute peripheral neutrophil count [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the associated increase in blood inflammatory markers upon CXCR2 inhibition warrants additional studies to fully understand the mode of action and therapeutic potential of this new treatment strategy in CF (Moss et al, 2013).…”
Section: Neutrophil-based Targeting Strategies and Their Implicationmentioning
confidence: 99%
“…These are in different stages of drug development and have been shown to have an effect on neutrophil recruitment to the lung in clinical studies (Holz et al, 2010;Lazaar et al, 2011;Virtala et al, 2012;Pavord et al, 2013). In addition, the effect of inhibiting neutrophil recruitment has been shown for clinical biomarkers and endpoints indicative of disease efficacy as investigated in cystic fibrosis, severe asthma, and COPD (Nair et al, 2012;Moss et al, 2013;Rennard et al, 2015). Despite a strong association of chemokine involvement in disease, to date, there are only two marketed products targeting chemokine receptors: plerixafor, a small-molecule antagonist of CXCR4, and maraviroc, an antagonist of CCR5 (Bachelerie et al, 2014).…”
Section: Abbreviations: Az10397767 (R)mentioning
confidence: 99%